Decontamination of dental implant surface in peri-implantitis treatment: A literature review - Mellado-Valero, Ana (Medicina Oral S.L., 2013)
Etiological treatment of peri-implantitis aims to reduce the bacterial load within the peri-implant pocket and decontaminate the implant surface in order to promote osseointegration. The aim of this literature review was to evaluate the efficacy of different methods of implant surface decontamination. A search was conducted using the PubMed (Medline) database, which identified 36 articles including in vivo and in vitro studies, and reviews of different decontamination systems (chemical, mechanical, laser and photodynamic therapies). There is sufficient consensus that, for the treatment of peri-implant infections, the mechanical removal of biofilm from the implant surface should be supplemented by chemical decontamination with surgical access. However, more long-term research is needed to confirm this and to establish treatment protocols responding to different implant characterics. Key words:Peri-implantitis, treatment, decontamination, implant surface, laser.